The Public's Interest in the Production of Tongbara Chili Sauce inKedonganan Village, Bali - Sipakkar, Reynhard Jopinus; Ary Pradana, Yoshua; Pradnya Paramita, Kadek; Ayu Hanifa, Adinda; Putu Wiweka Krisna Dewi, Ayu (PT. Artha GenetikaLab Indonesia, 2024)
Kedonganan Beach, located in Kuta District, is one of Bali's coastal areas with significant marine resource potential. Most of the local population works as fishermen due to the village's location, bordered by the sea on both the west and east sides. This makes the majority of its residents engaged in the fisheries and marine sectors, including as fishers. One of the fish species with high potential, and a primary catch for fishermen in the Kedonganan area, is tuna. The method used in this study involvedcollecting data through questionnaires distributed via Google Forms for greater efficiency. The goal of this research is to develop the